Analyse de la répartition spatiale des incendies de forêt en fonction des facteurs anthropiques, écologiques et biophysiques. Le cas de la forêt de la Mâamora (Maroc septentrional) - Khalid Cherki (Études Caribéennes)
Forest fires are the main disturbance and the degradation factor most devastating that can affect forested areas, especially in the Mediterranean basin when species are highly flammable and climate conditions are marginal. Morocco as a Mediterranean country is not spared from this phenomenon, thus 3000 ha of forest are burned every year, and this situation is aggravated by the low rate of regeneration and restoration of the unbalanced ecosystems such as the Mâamora. To mitigate this situation, the establishment of an effective management plan for forest fire prevention requires not only an intimate knowledge of environment but also a perfect analysis of fire phenomenon. Therefore in this study, we focused our diagnosis on the analysis of old fires occurred in the past in Mâamora forest. The study highlighted that human-forest interface areas (roads, villages) have no influence on fires occurrence. Besides it was shown that grazing practiced in a well-balanced way, could play a key role in reducing fire hazards. In addition the study reveals that fuel load of is the major factor that governs both fire ignition and fire spread of, this load is closely related to site quality (soil and rainfall)